A murderous marriage - Maxwell, Alyssa (Maxwell, Alyssa. Lady and lady's maid mysteries., 2019)
Since the Great War, the Renshaw family fortune has suffered, and Lady Julia Renshaw is under pressure to marry for money. She has settled on Gilbert Townsend, a much older viscount and wealthy industrialist. It<U+2019>s clear to her sister Phoebe that this is not a love match. Nevertheless, the wedding takes place<U+2014>and in a hurry. At the reception aboard the groom<U+2019>s yacht, there appears to be tension between Gil and several guests: his best man, a fellow veteran of the Boer War; his grouchy spinster sister; and his current heir, a nervous young cousin named Ernest. The bride is also less than pleased when she discovers that Gil<U+2019>s attractive young secretary will be escorting them on their honeymoon. The next morning, before the yacht can depart the harbor, Gil<U+2019>s body is found in the water below<U+2014>and Julia is the prime suspect. Now Phoebe and her maid Eva must discover who pushed him over before the Renshaws<U+2019> social standing is irreparably stained by murder.